Relations between southern Arabia and the northern Horn of Africa during the last millennium BC - Phillipson, David W. (Proceedings of the Seminar for Arabian Studies, 2011)
The long-standing view that colonization from southern Arabia had a major and long-lasting effect on the history of the northern Horn during the last millennium BC, notably the establishment in the latter area of a unified 'Pre-Aksumite' state, is examined critically. Recent archaeological research in both Ethiopia and Eritrea has demonstrated a far more diverse population in the northern Horn than was previously recognized. A significant degree of continuity from earlier times is also attested. Reconsideration of the epigraphic evidence leads the author to question the importance formerly attached to a polity named dʿmt. Links with southern Arabia are indisputable, but colonization was probably small-scale and short-lived.